Reproducibility of Structural and Diffusion Tensor Imaging in the TACERN Multi-Center Study - Prohl, Anna K.; Scherrer, Benoit; Tomas-Fernandez, Xavier; Filip-Dhima, Rajna; Kapur, Kush; Velasco-Annis, Clemente; Clancy, Sean; Carmody, Erin; Dean, Meghan; Valle, Molly; Prabhu, Sanjay P.; Peters, Jurriaan M.; et al. (Frontiers in Integrative Neuroscience, 2019)
Background: Multi-site MRI studies are often necessary for recruiting sufficiently-sized samples when studying rare conditions. However, they require pooling data from multiple scanners into a single data set, and therefore it is critical to evaluate the variability of quantitative MRI measures within and across scanners used in multi-site studies. The aim of this study was to evaluate the reproducibility of structural and diffusion weighted MRI measurements acquired on seven scanners at five medical centers as part of the Tuberous Sclerosis Complex Autism Center of Excellence Research Network (TACERN) multisite study. Methods: The American College of Radiology phantom was imaged monthly to measure reproducibility of signal intensity and uniformity within and across seven 3T scanners from General Electric, Philips, and Siemens vendors. One healthy adult male volunteer was imaged repeatedly on all seven scanners under the TACERN structural and diffusion weighted protocol (5 b=0 s/mm2 and 30 b=1000 s/mm2) over a period of 5 years (age 22-27 years). Reproducibility of inter- and intra-scanner brain segmentation volumes and diffusion tensor imaging metrics fractional anisotropy (FA) and mean diffusivity (MD) within white matter regions was quantified with coefficient of variation. Results: ACR Phantom signal intensity and uniformity were similar across scanners and changed little over time, with a mean intra-scanner coefficient of variation of 3.6% and 1.8%, respectively. The mean inter- and intra-scanner coefficients of variation of brain structure volumes derived from T1-weighted images of the human phantom were 3.3% and 1.1%, respectively. The mean inter- and intra-scanner coefficients of variation of FA in white matter regions were 4.5% and 2.5%, while the mean inter- and intra-scanner coefficients of variation of MD in white matter regions were 5.4% and 1.5%. Conclusions: Our results suggest that volumetric and diffusion tensor imaging measurements are highly reproducible between and within scanners and provide typical variation amplitudes that can be used as references to interpret future findings in the TACERN network.